Extramedullary Involvement of Myelofibrosis in the Colon: A Case Report - Krystal Mills; Naseema Gangat; Victor Chedid (Gastro Hep Advances)
Colitis refers to a range of inflammatory conditions of the colon and each condition requires a distinct diagnostic and therapeutic approach. Common differentials include inflammatory bowel disease, ischemic colitis, and infections. Endoscopic evaluation is often a critical adjunct in determining the underlying cause of colitis and concomitant biopsies further improve diagnostic accuracy. Work up of this clinical case revealed the diagnosis of extramedullary hematopoiesis presenting as colonic ulcers in a patient with myelofibrosis, which has not yet been described in the existing literature.